The Influence of Cyberpsychology of Online Gambling on Adolescent Mental Health and Digital Well-being - Risna Rahmawati; Zarina Akbar; Mira Aryani (Department of Psychology, Faculty of Education, Universitas Negeri Surabaya, 2025)
The rapid development of digital technology has led to new behavioral phenomena among adolescents, one of which is engagement in online gambling. From a cyberpsychology perspective, this study examines how adolescents’ interactions with the digital world particularly online gambling platforms affect their mental health and digital well-being. Cyberpsychology explains that interface design, reinforcement algorithms, and the illusion of control in online games can trigger addiction and reduce adolescents’ reflective awareness in using technology. As a result, they become more vulnerable to anxiety, depression, social isolation, and decreased self-esteem. Moreover, involvement in online gambling often leads to family conflicts, academic disruptions, and sleep disorders, all of which negatively impact their overall digital well-being. This study employs a literature review approach to explore the relationship between psychological factors in the digital space and their effects on adolescents’ mental conditions. Findings highlight the need for interventions based on digital literacy and emotional regulation strategies to build a healthier digital ecosystem for adolescents. Raising awareness of psychological dimensions in digital environments is crucial to preventing long-term negative effects. This study is expected to serve as a foundational reference for the development of preventive programs and policies targeting adolescents in the digital era.